Do Xylylenes Isomerize in Pyrolysis?. Issue 14 (23rd June 2020) - Hirsch, Florian; Pachner, Kai; Fischer, Ingo; Issler, Kevin; Petersen, Jens; Mitric, Roland; Bakels, Sjors; Rijs, Anouk M.
Abstract: We report infrared spectra of xylylene isomers in the gas phase, using free electron laser (FEL) radiation. All xylylenes were generated by flash pyrolysis. The IR spectra were obtained by monitoring the ion dip signal, using a IR/UV double resonance scheme. A gas phase IR spectrum of para‐xylylene was recorded, whereas ortho‐ and meta‐xylylene were found to partially rearrange to benzocyclobutene and styrene. Computations of the UV oscillator strength for all molecules were carried out and provde an explanation for the observation of the isomerization products. Abstract : A gas phase IR spectrum of para‐xylylene was recorded by IR/UV ion dip spectroscopy. The molecule was generated by flash pyrolysis. Ortho‐ and meta‐xylylene partially rearrange to benzocyclobutene and styrene. Their detection can be explained by the oscillator strength of the UV transition.